2021
DOI: 10.18388/abp.2020_5528
|View full text |Cite
|
Sign up to set email alerts
|

Ononin induces cell apoptosis and reduces inflammation in rheumatoid arthritis fibroblast-like synoviocytes by alleviating MAPK and NF-κB signaling pathways

Abstract: As a kind of chronic inflammatory diseases, Rheumatoid arthritis (RA) has a low cure rate and easy recurrence. It has widely reported that abnormal activation of mitogen-activated protein kinase (MAPK) and nuclear factor kappa-B (NF-κB) signaling pathways are associated with the development of RA inflammation. Blocking the inflammatory signaling pathways of rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) can delay the development of RA. Ononin is a natural isoflavone glycoside and plays a key role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Meng et al. ( 21 ) mentioned that ononin treatment showed effective in vitro antiarthritic activity. Pan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al. ( 21 ) mentioned that ononin treatment showed effective in vitro antiarthritic activity. Pan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Ononin, a natural isoflavone, is widely distributed in Astragalus membranaceus, Glycyrrhiza uralensis, Hedysarum and Pueraria lobata [ 25 , 26 ]. Based on previous studies, ononin has anti-inflammatory and apoptotic effects [ 18 , 27 , 28 ]. In this study, we used IL-1β (10 ng/ml)-induced chondrocytes as an OA model in vitro and hypothesized that ononin mediated inflammation during OA through targets or signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have widely reported that curcumin and resveratrol are potential therapeutic drugs for OA that inhibit the inflammatory response and oxidative stress in chondrocytes [ 31 , 32 ]. Studies have also shown that ononin can protect LPS-induced RF inflammatory cells and RAW 264.7 cells from damage [ 18 , 27 ]. In our study, ononin significantly inhibited the IL-1β-mediated enhancement of the inflammatory factors TNF-α and IL-6 in rat chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of UHPLC-QTOF-MS showed that Betaine, Albflorin, D-Tetrandrine, Ononin, Bergapten, Ligustilide, 3-butyl-1(3H)-Isobenzofuranone, 3-butylidene-1(3H)-Isobenzofuranone, Columbianetin, Levistilide A, Stigmasterol, Glycerin fatty acid ester, Dioctyl phthalate, Rutin, Liquiritin, Quercitrin, Glycyrrhizic acid were the major ingredients in SJT. Among them, D-Tetrandrine ( Li et al, 2018 ), Ononin ( Meng et al, 2021 ), Stigmasterol ( Ahmad et al, 2020 ), Rutin ( Sun et al, 2017 ), Liquiritin ( Zhai et al, 2019 ) were reported to have an anti-RA function in previous research, which suggested that SJT had the potential property of treating RA.…”
Section: Discussionmentioning
confidence: 99%